2018
DOI: 10.1177/0748730418796443
|View full text |Cite
|
Sign up to set email alerts
|

Light, Alertness, and Alerting Effects of White Light: A Literature Overview

Abstract: Light is known to elicit non–image-forming responses, such as effects on alertness. This has been reported especially during light exposure at night. Nighttime results might not be translatable to the day. This article aims to provide an overview of (1) neural mechanisms regulating alertness, (2) ways of measuring and quantifying alertness, and (3) the current literature specifically regarding effects of different intensities of white light on various measures and correlates of alertness during the daytime. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
129
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 138 publications
(249 reference statements)
5
129
0
Order By: Relevance
“…Underlying neuronal mechanisms therefore differ. Studies investigating alerting effects of light during daytime after sleep deprivation found significant effects while several studies in rested individuals did not for a review see . Sleep deprivation alters sleep pressure, suggesting that these levels are important for alerting effects of light .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Underlying neuronal mechanisms therefore differ. Studies investigating alerting effects of light during daytime after sleep deprivation found significant effects while several studies in rested individuals did not for a review see . Sleep deprivation alters sleep pressure, suggesting that these levels are important for alerting effects of light .…”
Section: Discussionmentioning
confidence: 96%
“…Our study did not demonstrate alerting effects of light after placebo ingestion, indicating that light under these circumstance does not induce alertness during daytime, confirming previous observations . This emphasizes differences between night and day, since alerting effects of light during the night have been reported (reviews in Ref …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Light exposure has a great neurobiological effect on humans such as pupil constriction and brain cognition . The intensity, timing, duration, and spectral characteristics of light all contribute to these effects . However, the related mechanism is still unclear, particularly the spectral influence on the neurobiological system.…”
Section: Introductionmentioning
confidence: 99%